ChemInform Abstract: Cross‐Coupling Between Aryl‐ and Alkenyldimethylsilanes and Organic Halides Promoted by a Copper(I) Iodide/Sodium Hydride/Ethylene Glycol System. Issue 52 (10th December 2015) - Takeda, Takeshi; Takeda, Yuichiro; Tsubouchi, Akira
Abstract: A versatile cross‐coupling reaction of aryl‐ and alkenylsilanes (I) with various organic halides (II) is developed furnishing the corresponding cross‐coupling products (III) in good to excellent yields.